La missione della Chiesa negli accordi concordatari dopo il Concilio Vaticano II (Stato, Chiese e pluralismo confessionale, 2023)
The “Church Mission” in the Concordats after the Vatican Council IIABSTRACT: The Concordat Policy of the Holy Seat went through an unexpected development after the Vatican Council II. The agreements subscribed over the last decades have indeed engaged with lots of European Countries, and the range expanded to the African and Asia continent. The new geography designed to this agreements also matches with innovations in the structure and content of them. This essay aims to analyze this innovation and its strict connection with the documents of the Vatican Council II, enlightening how this has determined a more theological view of the objectives through which the freedom of the Catholic Church defines and details itself. While the concordats of the first half of the past century accompanied, followed and enlarged the trajectory of the Church rights towards spiritualization, this new phase is, indeed, characterized by a theological placement of the interests, whose freedom is indeed the object of the protections granted by the Concordats, which are briefly expressed by the lemma “Church Mission”, found in the first articles of the Concordats. This lemma, in the conciliar texts, is characterized not only by a theological dimension, but also by its direct connection with religious freedom.Sommario: 1. Una premessa - 2. I precedenti e il contesto dottrinale - 3. I documenti conciliari - 4. La “missione della chiesa” negli accordi concordatari tra XX° e XXI° secolo - 5. Per qualche annotazione conclusiva.